Translation Procedure of Cultural Words of the First Episode of Gadis Kretek Series - Rika Virtianti; Yuliasari, Ria; Ferdias Prihatna Sari (Universitas Nasional, 2024)
ABSTRACT Translating movies is not just about changing words; it's about understanding the culture behind them. Cultural words, in particular, can be tricky for translators because they carry deep meanings rooted in a specific culture. This research was carried out using language analysis method with both Indonesian and English subtitle script of the first episode of Gadis Kretek series as the data. This research aims at finding out what cultural words used and what translation procedures applied in translating the cultural words. Cultural word classification theory by Alonso and Ponte is used to analyze the cultural words found in the subtitle and translation procedure theory by Newmark is used to find out what translation procedures are used in translating the cultural words. From the 56 cultural words found in the first episode of Gadis Kretek series, the most frequently discovered type of cultural word is stereotype, with the number of 22 words or 39,2%, whereas the least frequently discovered type of cultural word is cultural heritage, with only 1 word or 2% of the total cultural words. The other three types of cultural word namely society, languages and social interactions share the same number and percentage of eleven words or 19,6%. Among the twelve procedures suggested by the theory, only five specific ones are applied in translating this subtitle. The first most frequently applied procedure is literal translation with the number of 23 words or 41,1%. The second most frequently used procedure is cultural equivalent with the number of 18 words or 32,1%. The third most frequently used procedure is deletion with 11 words or 19,6%. And the two least used procedures are transference which is 3 words or 5,4% and neutralization which is only one or 1,8%.